Do princesses wear hiking boots? - Coyle, Carmela LaVigna; Gordon, Mike 1948 March 16-; Gordon, Carl (Flagstaff, AZ. Rising Moon, 2003)
When a little girl asks her mother about princesses, she learns that they are much like herself.
Keywords: Princesses -- Fiction; Self-perception -- Fiction; Mothers and daughters -- Fiction; Stories in rhyme